Phosphate glass fibres and their composites - Hossain, Kazi M. Zakir; Felfel, Reda M.; Grant, David M.; Ahmed, Ifty (Royal Society of Chemistry, 2016)
An overview of the research conducted utilising phosphate glass fibres (PGFs), their manufacturing processes and utilisation potential for biomedical applications is presented in this chapter. Phosphate glasses of varying compositions in the form of fibrous structures alone and as fibrous reinforcements within composites are discussed. This chapter also highlights the methodologies used for the manufacture of these resorbable glass fibres and their composites. The advantages of using bioresorbable fibres in terms of their mechanical, dissolution, ion release, and in vitro and in vivo biocompatibility properties for the replacement, augmentation, guidance and growth of both hard and soft tissue in repair applications are also presented.